Reliability of Railway Operation - Landex, Alex (Proceedings from the Annual Transport Conference at Aalborg University, 2012)
Delays in railway networks cause problems in the daily operation and result in reduced reliability of the railway operation. The article defines methods based on the two closely related concepts of regularity and punctuality. These methods cover the traditional measures for trains based on the realized and simulated operation but also more advanced methods that take the passengers’ experience into account. This is done by using passenger delay models that estimates the delays of the passengers based on train delays and knowledge about the passenger behavior. For high‐frequent operation, the traditional measures cannot describe the perceived service reliability of the passengers as passengers can travel with delayed trains without knowing of the delay. Here, the article presents other reliability measures. Using the presented reliability approaches, the article illustrates how the reliability of railway operation can be improved through reliability analyses.